Deadly cross - Patterson, James, 1947- (New York : Little, Brown and Company, 2020)
"A scandalous double homicide in the nation's capital opens the psychological case files on Detective Alex Cross. Until Kay Willingham's shocking murder inside a luxury limousine, the Georgetown socialite, philanthropist, and ex-wife of the sitting vice-president led a public life. Yet few, including her onetime psychologist, had any inkling of Kay's troubled past in the Deep South. Murdered alongside her is Randall Christopher, a respected educator whose political ambitions may have endangered both their lives. While John Sampson of DC Metro Police tracks Randall's final movements, Alex Cross and FBI Special Agent Ned Mahoney travel to Alabama to investigate Kay's early years."
Sequel to: Criss cross.
Keywords: Cross, Alex -- (Fictitious character) -- Fiction; African American detectives -- Fiction; Police -- Washington (D.C.) -- Fiction; Murder -- Investigation -- Fiction; Washington (D.C.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)